Penerapan PPh Final Pasal 4 Ayat 2 pada Jasa Notaris : Studi Kasus Kantor Notaris kota Medan Sumatera Utara - Lubis, Putri Kemala Dewi; Harahap, Evi Suryani; Fahrani, Meutia; Br. Ginting, Renata Olivia; Br. Kaban, Novita Sari (Innovative: Journal Of Social Science Research, 2024)
This research focuses on the Medan City Notary Office, but the results of these findings can be used as a basis for further research in other regions in Indonesia. This research uses a qualitative approach with an in-depth case study method to analyze the application of Final Income Tax Article 4 Paragraph 2 to notary services at the Medan City Notary Office, North Sumatra. Final Income Tax (PPh) Article 4 Paragraph 2 is one of the tax collection mechanisms in Indonesia which is imposed on certain types of income. Data collection was carried out through in-depth interviews with notaries and office staff involved in the taxation process, as well as direct observation of tax administration and reporting activities. To ensure the validity of the data, triangulation was carried out by comparing the results of interviews, observations and related documents. This research focuses on how notary offices in Medan understand, implement and face challenges in implementing Final Income Tax Article 4 Paragraph 2. The results of the research show that the application of Final Income Tax Article 4 Paragraph 2 to notary services at the Medan City Notary Office has been carried out in accordance with tax regulations applicable